Molecular Docking Analysis of Flavonoids from Syzygium cumini (L.) Skeels: Proapoptotic Potential as an Anticancer Mechanism - Aini, Nur Sofiatul; Ansori, Arif Nur Muhammad; Widyananda, Muhammad Hermawan; Kharisma, Viol Dhea; Murtadlo, Ahmad Affan Ali; Herdiansyah, Mochammad Aqilah; Rebezov, Maksim; Burkov, Pavel; Gudz, Petr; Derkho, Marina; Bezhinar, Tatyana; Maksimiuk, Nikolai; Sazali, Munawir; Purnobasuki, Hery; Rollando, Rollando; Khairullah, Aswin Rafif; Sucipto, Teguh Hari (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
Non-small cell lung cancer (NSCLC) presents a significant global health challenge, with its prevalence and mortality rates rising steadily. In Indonesia, Syzygium cumini (L.) Skeels, known for its flavonoid richness, has a long history in traditional medicine. However, its specific mechanisms of action against cancer, particularly in inducing apoptosis in NSCLC, have not been fully elucidated. This study utilized an in silico approach to evaluate the pro-apoptotic potential of S. cumini flavonoids against NSCLC by targeting key proteins: Bcl-2, Bax, and Caspase-3. We retrieved flavonoid structures from PubChem and protein data from the Research Collaboratory for Structural Bioinformatics Protein Data Bank (RCSB PDB). The drug-likeness of these compounds was assessed using Swiss ADME, adhering to Lipinski's rule of five, while their anti-NSCLC probability was predicted using PASS Online. Molecular docking and screening were performed with PyRx, and the results were visualized using Discovery Studio. Our findings identified epigallocatechin 3-O-gallate and ellagic acid as the most promising anti-NSCLC candidates. Ellagic acid demonstrated the strongest binding affinity to Caspase-3, suggesting a potent pro-apoptotic effect. Epigallocatechin 3-O-gallate, on the other hand, exhibited the lowest binding energy across multiple target proteins, particularly Bcl-2 and Bax, indicating its broad pro-apoptotic potential. These results collectively suggest that flavonoids from S. cumini may hold significant promise as a source of novel anti-NSCLC agents, warranting further in vitro and in vivo investigations.